2020
DOI: 10.21273/hortsci15128-20
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Safening of Bentazon by Melatonin in Sweetpotato (Ipomoea batatas)

Abstract: Weed competition is a main factor limiting sweetpotato [Ipomoea batatas (L.) Lam] production. Yellow nutsedge (Cyperus esculentus L.) is a problematic weed to control due to its ability to quickly infest a field and generate high numbers of tubes and shoots. Compounding this is the lack of a registered herbicide for selective postemergence control of yellow nutsedge. Research was conducted to evaluate the bentazon dose response of two sweetpotato cultivars and one advanced clone and to evaluate the plant hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…A similar response was reported by Caputo et al. (2020), where Beauregard had a greater tolerance to bentazon in vitro. The reduction in percentage plant injury when bentazon was tank mixed with melatonin could be associated with an improvement in herbicide tolerance and antioxidant activity.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A similar response was reported by Caputo et al. (2020), where Beauregard had a greater tolerance to bentazon in vitro. The reduction in percentage plant injury when bentazon was tank mixed with melatonin could be associated with an improvement in herbicide tolerance and antioxidant activity.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, the significant decrease in injury observed with some of the treatment combinations relative to mesotrione or bentazon alone is promising. When compared with results reported by Caputo et al (2020) in vitro, less injury due to bentazon was observed in Beauregard and Covington. Finally, the expected injury due to bentazon in the field might be less, since the plants would be hardier.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Melatonin widely participates in nature as a ubiquitous molecule, and its biological activity occurs in unicellular organisms, fungi, animals, and plants [ 33 , 34 ]. Melatonin can enhance the tolerance of plants to abiotic stresses, such as low chilling, drought, herbicides, heavy metals, and salt [ 35 , 36 , 37 , 38 , 39 , 40 ]. Under salt conditions, exogenous application of melatonin regulates a variety of genes and physiological processes involved in resistance to salt stress in plants [ 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%